Day 1 Mon, May 04, 2020 2020
DOI: 10.4043/30840-ms
|View full text |Cite
|
Sign up to set email alerts
|

Self-Certification and Safety Compliance for Robotics Platforms

Abstract: In this paper, the results and methodology of a framework to enable run-time safety compliance and self-certification of robotics is presented. This transferable framework is verified within a practical demonstration scenario, based on asset inspection within a confined space, and representing a Beyond Visual Line of Sight (BVLOS) use case. The methodology of the framework is based on computationally efficient analysis to support run-time, front-end, data analysis and adaptive decision-making. Utilizing the Hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…For the inspection aspect of our mission, we integrate FMCW radar to provide asset integrity inspection via surface and subsurface analysis. This novel application of FMCW includes detection of corrosion, on metal structures and integrity inspection of composite structure wind turbine blades [8], [18], [95].…”
Section: Design Of a Symbiotic Digital Architecture For Safety Compliance And Resilience In Autonomous Missionsmentioning
confidence: 99%
See 2 more Smart Citations
“…For the inspection aspect of our mission, we integrate FMCW radar to provide asset integrity inspection via surface and subsurface analysis. This novel application of FMCW includes detection of corrosion, on metal structures and integrity inspection of composite structure wind turbine blades [8], [18], [95].…”
Section: Design Of a Symbiotic Digital Architecture For Safety Compliance And Resilience In Autonomous Missionsmentioning
confidence: 99%
“…However, international safety regulators, such as the civil aviation authorities, have identified that run-time safety and reliability of autonomous systems are key obstacles in Beyond Visual Line of Sight (BVLOS) missions for unmanned aerial vehicles in twelve European countries [17]. We also highlight dynamic conditions, such as weather conditions, smoke, steam and mist, as challenges which reduce the reliability of sensors onboard robotic platforms [8], [18], [19]. Despite advancements in RAI, there are several barriers that limit expansion in the offshore domain, which include technological, regulatory and commercial challenges.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Trust in the reliability and resilience of these autonomous systems is paramount to their continued growth, as well as their safe and effective utilization [9][10][11]. Hauser [12] reported the need for autonomous systems operating in real-world conditions to radically are autonomous, semi or fully, and encompasses their advanced software and hardware components, and interactions with the surrounding environment.…”
Section: Introductionmentioning
confidence: 99%
“…The system was then demonstrated within an industry informed confined space mission for an offshore substation. In addition, a digital twin was utilized to communicate with the system and to analysis the system's outcome, which is not the scope of this paper [9]. Although we present and discuss the integrated models and technologies used in this autonomous mission, to provide a mission and autonomous system context, the main focus of this paper is on the modelling paradigm, based on ontologies [21], i.e., the system model.…”
Section: Introductionmentioning
confidence: 99%